تحضير بنية زيوليتية ودراسة تأثير المعالجة الحرارية في البنية المسامية (Latakia University Journal -Basic Sciences Series, 2018)
حضرنا بنية زيوليتية باستخدام سيليكات الصوديوم كمصدر للسيليكا،ونترات الألمنيوم كمصدر للألومينا. استخدمنا مركب إتوكسيلات الكحول كعامل موجه للبنية (SDA). تمت عملية التحضير بالمعالجة الهيدروحرارية للمزيج التفاعلي في مفاعل خاص عند الدرجة 2000C، ولمدة أربع ساعات. أعطيت العينة الناتجة الرمز Z-1، عولجت هذه العينة حرارياً عند الدرجة 5000C وأعطيت الرمز Z-1(500). أجرينا مقارنة بين خواص البنية المسامية لهاتين العينتين مع عينتين متشابهتين من حيث النركيب، ولكن إحداهما لم تخضع للمعالجة الهيدروحرارية Z-2، والأخرى هي نفسها العينة Z-2 ولكنها معالجة حرارياً عند الدرجة 5000C. درست العينات الناتجة باستخدام تقانة الامتزاز الحجمي لغاز الآزوت عند الدرجة 77K لتحديد خواص البية النسيجية، وتقانة التحليل الحراري التفاضلي والتحليل الحراري الوزني TG-DTA. وجدنا اختلافاً واضحاً بين خواص البنية المسامية للعينات الناتجة. تؤثر المعالجة الهيدروحرارية بشكل مباشر على البنية المسامية، وتقود إلى مساحة سطحية نوعية كبيرة (225 m2/g). تبين منحنيات التحليل الحراري التفاضلي آثاراً حرارية مختلفة، وتبدي العينات ثباتاً حرارياً كبيراً. We prepared a zeolitic structure, using sodium silicate as a source of silica, and aluminum nitrate as a source of alumina. We used the alcohol ethxylate compound as structure-directing agent (SDA). The hydrothermal treatment method was used for reaction mixture in special reactor at 2000C for 4h. The produced sample after hydrothermal treatment (Z-1) was treated at 5000C and symbolized as Z-1(500). These two samples had been compared with two other samples. The first Z-2 has the same composition of Z-1, but without hydrothermal treatment. This sample was treated at 5000C and symbolized as Z-2(500). The texture properties of the prepared samples were studied by absorption of N2 at 77K. The thermal effects on Z-1 and Z-2 samples were studied by DTA-TG technique. We found a clear difference in the porosity structure properties of the samples. The hydrothermal treatment has a direct influence in the porosity. This treatment gives a high specific surface area (225m2/g). The DTA-TG analysis shows different thermal effects. The structures show a high thermal stability.